A primary squamous cell carcinoma of the sigmoid colon in a young patient: A case report and literature review. Issue 8 (16th August 2022) - Faisal, Mohanad; Abdalhadi, Ahmed; Karzoun, M. Zaki; Mohamed, Mohamed Aboagla Suliman; Sharaf Elden, Mouhammad Zuhair; Shablak, Alaaeldin
Abstract: Colon cancer is among the most common types of cancer with adenocarcinomas being the most common type. Herein we report a young patient who presented with primary colonic squamous cell carcinoma without risk factors. To the best of our knowledge, this is the youngest patient with such diagnosis worldwide. Abstract : We reported a case of colon SCC in young patient to increase the awareness about this rare malignancy among oncologists with quick review about pathophysiology and management.